Experiment For Production Salted Eegg Using Nipah Leaf As Salt Replacement - Dewi Andriani; St. Hadijah (Program Studi Hospitality dan Pariwisata, 2018)
ABSTRACT The objective of the research is to find out the stem of nipah palm tree can be used as salt substitution in the process of making salted egg, the effect of the substitution and the reaction of the society to the product. The population was all students of Politechic Bosowa Batch 3, there was 80 students. This research used Simple Random Sampling and found 67 student as sample. The sample used was stem of nipah palm tree which was in concentration 0%, 100%, 75%, and 50%. The data analysis of this research was statistic univariat and statitic descriptive anaylisis. The result of the research is using of stem of nipah palm tree as salt substituon can be accepted by the society as the data showed there was satisfactionand the increasing data in every experiment, and there was a benefit effect of stem og nipah palm tree to the process of making salted egg product, it was the value of stem of nipah palm tree was higher than the value of salted egg in control. Keywords: Salted Egg, Stem Of Nipah Palm Tree, Organoleptic Test.